2018
DOI: 10.1111/bph.14504
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ (N/OFQ) conjugated to ATTO594: a novel fluorescent probe for the N/OFQ (NOP) receptor

Abstract: Background and PurposeThe nociceptin/orphanin FQ (N/OFQ) receptor (NOP) is a member of the opioid receptor family and is involved in a number of physiological responses, pain and immune regulation as examples. In this study, we conjugated a red fluorophore‐ATTO594 to the peptide ligand N/OFQ (N/OFQATTO594) for the NOP receptor and explored NOP receptor function at high (in recombinant systems) and low (on immune cells) expression.Experimental ApproachWe assessed N/OFQATTO594 receptor binding, selectivity and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…The sequencing of PCR products revealed that NOP receptor transcripts from immune cells and brain were identical (115,116). Some studies detected the NOP receptor mRNA transcripts in leukocytes at levels comparable to those in human cerebral cortex (115), whereas others found them at very low amounts (88,121). Together, opioid receptor mRNAs appear to be expressed at relatively low levels in immune cells as compared to neuronal tissue or opioid receptor-expressing immune cell lines (88-91, 109, 110, 121, 122).…”
Section: Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing of PCR products revealed that NOP receptor transcripts from immune cells and brain were identical (115,116). Some studies detected the NOP receptor mRNA transcripts in leukocytes at levels comparable to those in human cerebral cortex (115), whereas others found them at very low amounts (88,121). Together, opioid receptor mRNAs appear to be expressed at relatively low levels in immune cells as compared to neuronal tissue or opioid receptor-expressing immune cell lines (88-91, 109, 110, 121, 122).…”
Section: Immune Cellsmentioning
confidence: 99%
“…NOP receptor protein detection appears variable, with high affinity radiolabeled N/OFQ binding in granulocytes (116), but lack of such binding in PBMC (88) from human blood. The latter research group recently detected NOP receptor binding (reversible by selective NOP receptor antagonist SB-612111) in human blood granulocytes using a novel fluorescent probe for the receptor (a red fluorophore-ATTO594 conjugated to the N/OFQ) (121).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Collectively these results can be interpreted assuming that βarr2 acts [as demonstrated for several GPCRs ( Gurevich and Gurevich, 2019 )] as a desensitizing element of the antinociceptive response to mu opioid as well as NOP receptor agonists. Of note, NOP receptor phosphorylation and internalization have already been described by different research groups ( Spampinato et al, 2001 ; Corbani et al, 2004 ; Zhang et al, 2012 ; Bird et al, 2018 ; Mann et al, 2019 ). βarr2( − / − ) mice were slightly less sensitive than βarr2(+/+) mice to the effects of Ro 65-6570 in the rotarod, with the 3 mg/kg dose being active in wild-type animals but not in mice lacking the βarr2 gene.…”
Section: Discussionmentioning
confidence: 76%
“…Male CD-1 mice (ENVIGO, Udine, Italy) were used in this study together with mice knockout for the NOP receptor gene [NOP(−/−)] and βarr2(+/+) and βarr2(−/−) mice. Details about the generation of NOP(−/−) mice have been published previously (Nishi et al, 1997;Bertorelli et al, 2002), moreover NOP(+/+) and NOP(−/−) mice have been backcrossed on CD-1 strain in our laboratories. βarr2(−/−) mice were from The Jackson Laboratory [JAX stock #011130; (Bohn et al, 1999)] and C57BL/6J mice were used as controls.…”
Section: Animalsmentioning
confidence: 99%
“…Then the ruminal epithelium cells were incubated with goat anti-rabbit IgG conjugated with FITC (1:200; Beyotime Institute of Biotechnology, Shanghai, China) at room temperature for 30 min and counterstained with Hoechst 33258 (Beyotime) ( 23 ). Finally, the coverslips (YA0774; Solarbio) were sealed with glycerol (MB9893; Meilun), and the samples were observed by laser confocal microscopy (FV500, OLYMPUS, China) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%